Treatment of Palmar Hyperhidrosis: T(4) Level Compared With T(3) and T(2) - Chang, Yu-Tang (2007)
OBJECTIVE: The aim of this study was to compare the outcomes of 3 different levels of sympathectomy. SUMMARY BACKGROUND DATA: Most surgeons still perform T(2) or T(2–3) sympathectomy for palmar hyperhidrosis, but both these treatments can cause severe side effects. Some recent articles have advocated T(4) sympathectomy and obtained satisfactory results. METHODS: Between January 2000 and August 2004, 234 records of patients treated for palmar hyperhidrosis were retrospectively reviewed. Of them, 86 patients were treated with endoscopic thoracic sympathectomy of T(2) (ETS(2)), 78 patients with ETS(3), and 70 patients with ETS(4). Follow-up data were collected using a telephone questionnaire with a scoring system. Multiple linear regressions were used to model markers for degree of satisfaction and severity of compensatory sweating (CS), including descriptive data, level of sympathectomy, clinical outcomes, and postoperative complications. RESULTS: Mean follow-up was 47.1 ± 17.2 months. All 3 levels of sympathectomy could have achieved comparable improvement of palmar hyperhidrosis (P = 0.162). However, 88.5% of the patients noticed CS. Patients with ETS(4) presented the lowest incidence of CS (P = 0.030), had the least severity of CS (β = −1.537, P = 0.002), and felt the least palmar overdryness (P < 0.001). None expressed regret for the procedure in the ETS(4) group (P = 0.022). Being obese did not increase the incidence of CS, but the severity of CS was directly related to body mass index (β = 0.917, P < 0.001). The patients would be more satisfied if the severity of CS was minimal (β = −0.185, P = 0.002). The degree of satisfaction may decrease with time (β = −0.025, P = 0.003) and was lower when their palms were overdry (β = −1.463, P < 0.001). CONCLUSIONS: Different from the current procedure of T(2) or T(3) sympathectomy for palmar hyperhidrosis, T(4) sympathectomy would be a better and more effective procedure with minimal long-term complications.